Role of Quantum Coherence and Energetic Disorder on Exciton Transport in Polymer Films - Barford, W; Duffy, C (2006)
The cross-over from coherent to incoherent exciton transport in disordered polymer films is studied by computationally solving a modified form of the Redfield equation for the exciton density matrix. This theory models quantum mechanical (ballistic) and incoherent (diffusive) transport as limiting cases. It also reproduces Forster transport for certain parameter regimes. Using model parameters appropriate to polymer thin films it is shown that short-time quantum mechanical coherence increases the exciton diffusion length. It also causes rapid initial energy relaxation and larger line widths. The route to equilibrium is, however, more questionable, as the equilibrium populations of the model do not satisfy the Boltzmann distributions over the site energies. The Redfield equation for the dimer is solved exactly to provide insight into the numerical results.